2018 IEEE Globecom Workshops (GC Wkshps) 2018
DOI: 10.1109/glocomw.2018.8644201
|View full text |Cite
|
Sign up to set email alerts
|

IOTA Feasibility and Perspectives for Enabling Vehicular Applications

Abstract: The emergence of distributed ledger technologies in the vehicular applications' arena is decisively contributing to their improvement and shaping of the public opinion about their future. The Tangle is a technology at its infancy, but showing enormous potential to become a key solution by addressing several of the blockchain's limitations. This paper focuses on the use of the Tangle to improve the security of both in-vehicle and off-vehicle functions in vehicular applications. To this end, key operational perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Overko et al [61] present a distributed reinforcement learning system based on IOTA to determine an unknown distribution of traffic patterns in a city. The limitations and potential impact of IOTA in ITS are also studied by Bartolomeu et al in [62]. They propose the use of this DLT to improve the security of both in-vehicle and off-vehicle functions.…”
Section: B Related Workmentioning
confidence: 98%
“…Overko et al [61] present a distributed reinforcement learning system based on IOTA to determine an unknown distribution of traffic patterns in a city. The limitations and potential impact of IOTA in ITS are also studied by Bartolomeu et al in [62]. They propose the use of this DLT to improve the security of both in-vehicle and off-vehicle functions.…”
Section: B Related Workmentioning
confidence: 98%
“…DAG-based TES showed better results as compared to Blockchain-based TES in terms of scalability and latency. IOTA DAG-based vehicular system was presented in [103] to improve trasactions latency. It is concluded that the transactions delay in IOTA is influenced by two main factors; tip selection algorithm and proof of work.…”
Section: B Directed Acyclic Graphmentioning
confidence: 99%
“…Barttholomy et al have used of tangle technology to improve the safety and efficiency of cars in the VANET. They introduced and analyzed tangle as a solution to the Blockchain problems in the VANET [37]. Kang et al proposed a Blockchain-based structure for VANET that miners are selected based on their cooperation in this system.…”
Section: Blockchain-based Decentralized Data Managementmentioning
confidence: 99%
“…As mentioned in [37], Barttholomy et al have used tangle technology to improve the safety and efficiency of cars in the VANET. They introduced and analyzed tangle as a solution to the Blockchain problems in the VANET.…”
Section: Comparisonmentioning
confidence: 99%